Impact of Social Media Marketing and Collaboration with Influencers in the Beauty Industry in Colombia - Alvis Góme, Natalia (SCT Proceedings in Interdisciplinary Insights and Innovations, 2024)
This research article examines the importance of social media marketing strategies and collaboration with influencers in the beauty industry in Colombia. Social media has reached significant penetration in Colombia, with over 32.9 million users in 2021. Platforms such as Instagram, Facebook, and YouTube are especially relevant in the beauty sector, allowing companies to expand their reach, interact directly with customers, and effectively position their brands. Paid advertising options on social media offer beauty companies the ability to increase their visibility and generate significant conversions. Advertising, along with advanced targeting and detailed performance metrics, enables companies to maximize their advertising return on investment, reaching highly specific audiences and increasing the effectiveness of their.